STUDI ISLAM DALAM PENDEKATAN GENDER - Asriana Harahap; Hilda Wahyuni (Jurnal Kajian Gender dan Anak, 2021)
People often compare men and women based on physiology and biology, causing differences gender. Gender differences mostly impact discrimination, violence and harassment on the assumption that women are weak. This thinking occurs a lot in the community as a result of socio-customary construction. The difference between the two groups is not profitable in one individual or group. The Islamic creed protects the rights of women so that it provides care and respect. The practice becomes unnatural to women because Islamic teachings and guidance are not implemented, the cause of the developing tradition is very far from Islam. Gender differences do not become a problem for free to do anything while not deviating from religious teachings such as female leadership, polygamy, and inheritance.Keywords: Gender, Islam, ImplementationAbstrakMasyarakat sering bandingkan kaum adam dan hawa berdasarkan fisiologis dan biologis sehingga menyebabkan bias gender. Bias gender kebanyakan berdampak diskriminasi, kekerasan dan pelecehan dengan anggapan perempuan itu lemah. Pemikiran ini banyak terjadi ditengah masyarakat hasil dari kontruksi sosial-adat. Perbedaan kedua kaum tidak mencorakkan untung disatu individu maupun kelompok. Akidah Islam menjaga hak kaum hawa sehingga memberi kepedulian dan posisi tehormat. Praktek menjadi tidak wajar terhadap perempuan karena ajaran serta bimbingan Islam tidak di implementasikan, disebabkan tradisi yang berkembang sangat jauh dari Islam. Perbedaan gender tidak menjadi masalah untuk bebas melakukan hal apapun selagi tidak melenceng dari ajaran agama seperti kepemimpinan perempuan, poligami, dan kewarisan.